Customer Relationship Management And Social Media Determine Sharia Bank Client Loyalty: Customer Relationship Management Dan Media Sosial Menentukan Loyalitas Nasabah Bank Syariah - Helen Arinatha Solihin; Yulfiswandi Yulfiswandi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Digital transformation actively drives the Islamic financial sector to adopt advanced online marketing strategies. Specific Background Customer relationship management and social media platforms function as essential interactive communication channels that build consumer trust alongside business sustainability. Knowledge Gap Previous literature frequently examines relational strategies and digital networks in isolation, leaving their combined mechanisms on buyer retention relatively underexplored. Aims This quantitative study evaluates how customer relationship management and social media determine client loyalty, positioning consumer gratification as a mediating variable within Sharia institutions. Results Data collected from 214 qualified customers in Batam City and analyzed via SmartPLS 4 reveal that relational frameworks and digital networking positively dictate user satisfaction and devotion. Furthermore, customer satisfaction actively mediates the structural linkage connecting these interactive channels to long-term buyer retention. Novelty This research integrates relational management and digital operations into a unified structural model, specifically localized for the Batam City demographic. Implications Financial institutions must continuously deploy transparent digital services and responsive communication to sustain long-term client devotion in competitive markets. Highlights Relational strategies significantly shape user satisfaction within Islamic financial institutions. Digital networking platforms directly build consumer gratification alongside long-term trust. Gratification strictly mediates the linkage connecting interactive marketing channels to buyer devotion. Keywords Customer Relationship Management; Social Media; Customer Satisfaction; Sharia Banking; Consumer Loyalty